Adjustment or transformation? Disaster risk intervention examples from Austria, Indonesia, Kiribati and South Africa. (September 2022) - Fekete, Alexander; Fuchs, Sven; Garschagen, Matthias; Hutter, Gérard; Klepp, Silja; Lüder, Catharina; Neise, Thomas; Sett, Dominic; von Elverfeldt, Kirsten; Wannewitz, Mia
Abstract: Change triggered by natural hazards such as pluvial and coastal floods, sea-level rise as well as risks resulting from water scarcity are highly dynamic and related to the effects of ongoing climate change. Whether and how societies adapt, adjust, change, or transform because of climate change and related risks, is a currently debated topic. This question demands revisiting and comprehensively addressing existing theoretical foundations of transformations in risk management strategies and in risk governance to find effective ways to deal with climate change effects and their social consequences. Hence, the paper discusses current developments in transformation research and exemplifies this discussion with four interdisciplinary cases, which the co-authors reported in previous publications. Findings from Austria include a governance change within flood risk management related to zonation. Relocation in Indonesia and Kiribati showcases its cultural, behavioural as well as economic implications. Water scarcity in South Africa underlines the importance of behavioural change to enable the structural storage of rainwater. This paper analyses aspects of adjustment or transformation in these four examples. This may inform risk managers, decision-makers, practitioners, and planners dealing with natural hazards related to climate change how to conceptualise their (re-)actions. Highlights: Differences between the terms adaptation, adjustment, change, and transformation are analysed and working definitions suggested. Triggers and interventions are analysed whether they express adaptation, adjustment, or transformation. Empirical cases are re-analysed whether the changes therein exhibit elements of adaptation, adjustment, or transformation.